Development of a Monte Carlo ad hoc routing protocol for connectivity improvement - Perold, Philippus Rudolf (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.